Can They Hack It? - Liang Xiao (Beijing Review, 2023)
On July 13, senior Chinese diplomat Wang Yi and U.S. Secretary of State Antony Blinken met for the second time in less than a month on the sidelines of the Association of Southeast Asian Nations (ASEAN) Foreign Ministers' Meeting and related meetings in Jakarta, Indonesia. Blinken, who was supposed to visit Beijing days later in a bid to start repairing the heavily damaged China-U.S. relations, postponed his trip citing related concerns. Earlier, U.S. tech giant Microsoft had said on July 11 that "a China-based group was targeting Western government data.".